Bio-instructive hydrogel expands the paracrine potency of mesenchymal stem cells. (8th July 2021) - Drzeniek, Norman M; Mazzocchi, Andrea; Schlickeiser, Stephan; Forsythe, Steven D; Moll, Guido; Geißler, Sven; Reinke, Petra; Gossen, Manfred; Gorantla, Vijay S; Volk, Hans-Dieter; Soker, Shay
Abstract: The therapeutic efficacy of clinically applied mesenchymal stromal cells (MSCs) is limited due to their injection into harsh in vivo environments, resulting in the significant loss of their secretory function upon transplantation. A potential strategy for preserving their full therapeutic potential is encapsulation of MSCs in a specialized protective microenvironment, for example hydrogels. However, commonly used injectable hydrogels for cell delivery fail to provide the bio-instructive cues needed to sustain and stimulate cellular therapeutic functions. Here we introduce a customizable collagen I-hyaluronic acid (COL-HA)-based hydrogel platform for the encapsulation of MSCs. Cells encapsulated within COL-HA showed a significant expansion of their secretory profile compared to MSCs cultured in standard (2D) cell culture dishes or encapsulated in other hydrogels. Functionalization of the COL-HA backbone with thiol-modified glycoproteins such as laminin led to further changes in the paracrine profile of MSCs. In depth profiling of more than 250 proteins revealed an expanded secretion profile of proangiogenic, neuroprotective and immunomodulatory paracrine factors in COL-HA-encapsulated MSCs with a predicted augmented pro-angiogenic potential. This was confirmed by increased capillary network formation of endothelial cells stimulated by conditioned media from COL-HA-encapsulated MSCs. Our findings suggest that encapsulation of therapeutic cells in a protective COL-HA hydrogel layer provides the necessary bio-instructive cues to maintain and direct their therapeutic potential. Our customizable hydrogel combines bioactivity and clinically applicable properties such as injectability, on-demand polymerization and tissue-specific elasticity, all features that will support and improve the ability to successfully deliver functional MSCs into patients.